2015
DOI: 10.1038/srep09153
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Hollow CuO@SiO2 Spheres and Its Catalytic Performances for the NO + CO and CO Oxidation

Abstract: The hollow CuO@SiO2 spheres with a mean diameter of 240 nm and a thin shell layer of about 30 nm in thickness was synthesized using an inorganic SiO2 shell coating on the surface of Cu@C composite that was prepared by a two-step hydrothermal method. The obtained hollow CuO@SiO2 spheres were characterized by ICP-AES, nitrogen adsorption-desorption, SEM, TEM, XRD, H2-TPR, CO-TPR, CO-TPD and NO-TPD. The results revealed that the hollow CuO@SiO2 spheres consist of CuO uniformly inserted into SiO2 layer. The CuO@Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Among the studied core‐shell structured nanocatalysts, catalysts with silica or silicate shell are of great interest because of the abundant resource, adjustable surface areas and particle sizes, tailorable pore sizes and structures, diverse morphologies, easy functionalization and colloidal stability of silica or silicate ,,. Due to the critical role played by nanoscale copper in some important catalytic reactions such as electrocatalysis, photocatalysis, gas‐phase catalysis, and liquid‐phase catalysis, core‐shell structured nanocatalysts with copper species as single core or multiple cores have received extensive research interest, and several studies have demonstrated their superior catalytic performance compared to traditional supported catalysts ,. However, research on core‐shell structured Cu@SiO 2 nanocatalysts has not progressed much compared to core‐shell structured noble metal/silica nanocatalysts, such as Au@SiO 2 and Ag@SiO 2 .…”
Section: Introductionmentioning
confidence: 84%
“…Among the studied core‐shell structured nanocatalysts, catalysts with silica or silicate shell are of great interest because of the abundant resource, adjustable surface areas and particle sizes, tailorable pore sizes and structures, diverse morphologies, easy functionalization and colloidal stability of silica or silicate ,,. Due to the critical role played by nanoscale copper in some important catalytic reactions such as electrocatalysis, photocatalysis, gas‐phase catalysis, and liquid‐phase catalysis, core‐shell structured nanocatalysts with copper species as single core or multiple cores have received extensive research interest, and several studies have demonstrated their superior catalytic performance compared to traditional supported catalysts ,. However, research on core‐shell structured Cu@SiO 2 nanocatalysts has not progressed much compared to core‐shell structured noble metal/silica nanocatalysts, such as Au@SiO 2 and Ag@SiO 2 .…”
Section: Introductionmentioning
confidence: 84%
“…From the perspective of particle shape or morphology, the improved ERC could be attributed to the creation of active edges, grain boundaries, and steps. [59] Various morphologies, such as spherical or pseudospherical nanoparticles (NPs), [60][61][62] nanocubes (NCs), [63] nanosheets (NSs), [64] nanowires (NWs), [65][66][67] hollow cages, [68,69] multi-pods, [70] hierarchical structures, [71][72][73] and different polyhedral including cubes, [74][75][76] cuboctahedra, [77] octahedra, [78][79][80] truncated octahedra, [81][82][83] dodecahedra, [84,85] and so forth, have been explored over the years. The conventional NPs form of Cubased electrocatalysts (CuNPs) is expected to preferentially form C2 compounds due to the combination of two critical parameters, i. e. (i) low co-ordination sites and (ii) low crystals facets on the Cu surface.…”
Section: Morphology Dependent Cu-based Co 2 Reductionmentioning
confidence: 99%
“…Platinum (Pt) functionalized NiO hollow tube exhibited remarkable selectivity of C 2 H 5 OH sensing against CO and H 2 gases [32]. The hollow structure of CuO@SiO 2 exhibits excellent catalytic activities toward CO and NO oxidation compared with individual CuO and SiO 2 [33]. Besides, carbon nanotube catalyst could raise the selectivity of H 2 production rather than CO [34].…”
Section: Introductionmentioning
confidence: 99%